2015
DOI: 10.1002/aenm.201500300
|View full text |Cite
|
Sign up to set email alerts
|

Thieno[3,2‐b][1]benzothiophene Derivative as a New π‐Bridge Unit in D–π–A Structural Organic Sensitizers with Over 10.47% Efficiency for Dye‐Sensitized Solar Cells

Abstract: Three new thieno[3,2‐b][1]benzothiophene (TBT)‐based donor–π–acceptor (D–π–A) sensitizers, coded as SGT‐121, SGT‐129, and SGT‐130, have been designed and synthesized for dye‐sensitized solar cells (DSSCs), for the first time. The TBT, prepared by fusing thiophene unit with the phenyl unit of triphenylamine donor, is utilized as the π‐bridge for all sensitizers with good planarity. They have been molecularly engineered to regulate the highest occupied molecular orbital (HOMO)‐lowest unoccupied molecular orbital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
73
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(77 citation statements)
references
References 60 publications
4
73
0
Order By: Relevance
“…[6][7][8][9][10][11][12] Highefficiency low-cost DSCs are required to be able to commercialize this technology.O ne way of achieving such goal is through the development of dye molecules,which can harvest more photons while maintaining high photovoltages. [13][14][15] In this regard, systematic studies on the structure-electrochemical property relationship are critically important. [16][17][18][19][20][21][22] Moreover, the reported systematic studies on DSCs were mostly assembled with cobalt or iodine electrolyte,l imiting the attainable open-circuit voltage (V OC ).…”
mentioning
confidence: 99%
“…[6][7][8][9][10][11][12] Highefficiency low-cost DSCs are required to be able to commercialize this technology.O ne way of achieving such goal is through the development of dye molecules,which can harvest more photons while maintaining high photovoltages. [13][14][15] In this regard, systematic studies on the structure-electrochemical property relationship are critically important. [16][17][18][19][20][21][22] Moreover, the reported systematic studies on DSCs were mostly assembled with cobalt or iodine electrolyte,l imiting the attainable open-circuit voltage (V OC ).…”
mentioning
confidence: 99%
“…The order of the electron lifetime was in line with the V oc values of ZL005 (808 mV) and ZL003 (957 mV). The highest electron lifetime ( τ hr = 1/ω min = 2πƒ max ) was calculated from the midfrequency region of the Bode plots (Figure b), and it was obvious that the value of τ hr for ZL003 was greater than that of ZL005; hence, the ZL003‐based DSSC had longer electron lifetime, which indicated that ZL003 has more effective suppression of back reaction of injected electrons from Co 3+ ions. Therefore, it is reasonable to conclude that ZL003 gives a higher V oc compared with ZL005, which yields a higher device efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…The average lifetime of ZL003 absorbed onto Al 2 O 3 films and TiO 2 films was 5.15 and 0.51 ns, respectively, whereas the average lifetime of ZL005 was 4.67 ns on Al 2 O 3 films and 0.85 ns on TiO 2 films. From the comparison of the PL decays for TiO 2 and Al 2 O 3 samples, we estimated the electron injection efficiencies of the dyes using Equation ηinj=1τTio2τAl2O3…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Typically, organic sensitizers consist of an electron donating group, a π-conjugated bridge and an electron accepting unit. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] In addition, an anchoring group (usually comprising a carboxylic acid moiety, COOH) is introduced, that allows the chemical adsorption of the dye on the metal-oxide semiconductor.…”
Section: Introductionmentioning
confidence: 99%